LEGAL POSITION OF RESTORATIVE JUSTICE IN QANUN JINAYAT - Muhammad Ihsan (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2020)
The penal theory that exists is basicly aimed at achieving justice, therefore the achievement model can be devide into two models, namely the retributive justice model and the restorative justice model. The retributive justice model establish justice based on the philosophy of retaliation, while the restorative justice model is based on the philosophy of recovery. In the case of criminalization in the Criminal Code which is also maintained in the Qanun Jinayat, the philosophy of justice adopted is the first model. Thus, in the convictions of cases of offenders of jinayat offenses, Qanun Jinayat also emphasizes the principle of retributive justice. Meanwhile, the concept of restorative justice in the criminal law system in Indonesia is only applied to cases of children who are dealing with the law and are also adopted by Qanun Jinayat. The concept of restorative justice is basically not known in the Aceh Qanun Jinayat, namely Qanun Number 6 of 2014, but based on the sound of Article 66 of this qanun